Experimental investigation of a novel vertical axis wind turbine with pitching and self-starting function. (1st August 2020) - Su, Hao; Dou, Bingzheng; Qu, Timing; Zeng, Pan; Lei, Liping
Highlights: A novel vertical axis wind turbine with rotatable auxiliary blades is made. Wind tunnel experiments are carried out for the proposed wind turbine. The geometric characteristic of the proposed wind turbine provides better self-starting performance. The maximum power coefficient can be reduced by 63.1% at 0° pitch angle. Constant output power at different wind speeds is realized through pitch control. Abstract: Wind, as a renewable, cost-competitive, and no air-pollution energy source, has caught worldwide attention. As a result of defective performance and backwardness in research, vertical axis wind turbines leg behind horizontal axis wind turbines in terms of commercial application, especially for large-scale wind turbines. In the present study, a new type of straight-bladed vertical axis wind turbine consisting of three pairs of blades has been introduced and tested in a wind tunnel to verify the reliability and efficiency of the novel configuration. There is a fixed main blade and a rotatable auxiliary blade (with different chord and span lengths from that in the main blade) in each pair of the blades. The experimental results demonstrate that the static torque coefficient of the proposed rotor is positive at all azimuthal angles and significantly higher than that of the traditional H-type rotor, which shows better self-starting performance. The proposed wind turbine can obtain a higher power coefficient compared to a traditional three-blade H-type rotor under the wind speeds varying from 4.54 m/s to 8.82 m/s. Besides, the power output of the wind turbine can be effectively controlled through the auxiliary blades pitching, and constant power output can be achieved in varying wind speeds.